THE INCIDENCE OF ED AFTER TURP AND TVP ON BPH PATIENTS - Alpendri, Aries; Utomo, Tjahyo Kelono; Utomo, Trisula; Singodimedjo, Prawito (Indonesian Urological Association, 2012)
Objective: The aim of this study was to know the incidence of erectile dysfunction (ED) after transurethral resections of the prostate (TURP) and transvesical prostatectomy (TVP). Material & method: Data were collected in 1 year period from January until December 2005 with cross sectional study design. There were 60 patients who met the inclusion and exclusion criteria and patient who participated in this study underwent TURP and TVP and divided in TURP group and TVP group. Erectile Dysfunction measured by International Index of Erectile Function-5 (IIEF-5) data was analyzed by statistic chi-square and independent t-test. Results: Sixty patients include this study with 30 patients in each group. The mean age of TURP was 64 ± 5,68 and TVP was 63,23 ± 4,83 with age ranging from 50 – 70 years. The incidence of ED after TURP and TVP was 36,67% and 16,70% respectively with p = 0,08. The IIEF-5 scores for TURP and TVP was 19,40 ± 3,95 and 21,03 ± 2,57 respectively and by statistical analysis the differences was not significant. Conclusion: The incidence of ED after TURP showed higher than TVP and by statistical analysis the differences was not significant. Keywords: Benign prostatic hyperplasia, erectile dysfunction, transurethral resection of the prostate, transvesical prostatectomy.